Feindliche Übernahme?: Krankenhauspflege in Zeiten der Ökonomisierung - Starystach, Sebastian; Bär, Stefan (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2019)
The current research concerning the commodification processes within the German public health care sector assumes that economic principles, which were introduced to the systemic and organizational level, will also diffuse to the daily practice of health care. With the help of a qualitative analysis, this paper examines the extent to which economic principles are gaining in importance in the mind-set of hospital nursing staff. The commodification theory of Schimank and Volkmann serves as the theoretical framework. The analysis shows that economic principles are normatively rejected and are not systematically applied. Although nurses perceive diffuse economic pressure on the level of working conditions, concerning their medical task they still act according to their professional ethos. Traditional regulatory principles stand in the way of a seamless institutionalization of economic orientations in health care. The theoretical conclusion is that the explanatory model could benefit from taking greater account of the mechanisms of re-production and de-institutionalization of existing regulatory principles. Overall, however, the analysis shows that in particular the commodification scale proposed by Schimank and Volkmann is an instructive heuristic tool for investigating dynamics of commodification.